2002
DOI: 10.1093/emboj/21.6.1497
|View full text |Cite
|
Sign up to set email alerts
|

Transfection-mediated generation of functionally competent Tula hantavirus with recombinant S RNA segment

Abstract: Since the discovery of RNA recombination in polioviruses, there has been a general belief that this mechanism operates only in positive-sense RNA viruses. Recently, studying wild-type Tula hantavirus, we observed a mosaic-like structure of the S RNA segment that was consistent with generation by recombination between viruses from two genetic lineages. Here we show transfection-mediated rescue of Tula virus carrying recombinant S RNA segment. Independent attempts yielded S RNA molecules of similar structure; th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 28 publications
1
42
0
Order By: Relevance
“…The mapping results and previous findings lead us to propose a model in which both Gn and Gc, by their cytoplasmic tails, mediate binding to the RNP. Additionally, our data suggest that the N protein of PUUV interacts with Gn-and Gc-CTs of several hantavirus types, thus in theory enabling generation of reassortants via CT recognition of closely related viruses (Plyusnin et al, 2002;Razzauti et al, 2009). …”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The mapping results and previous findings lead us to propose a model in which both Gn and Gc, by their cytoplasmic tails, mediate binding to the RNP. Additionally, our data suggest that the N protein of PUUV interacts with Gn-and Gc-CTs of several hantavirus types, thus in theory enabling generation of reassortants via CT recognition of closely related viruses (Plyusnin et al, 2002;Razzauti et al, 2009). …”
Section: Discussionmentioning
confidence: 77%
“…Furthermore, the M segments have been shown to reassort upon cell-culture gene transfections (Plyusnin et al, 2002). Therefore, we studied whether the PUUV bacN and RNP are able to recognize Gn-CT peptides of different hantavirus strains.…”
Section: Puuv N Binds To Gn-and Gc-ct Peptides Of Different Hantavirusesmentioning
confidence: 99%
“…However, intragenic recombination was considered being rare in negative-strand RNA virus (NSRV), including important human pathogens such as influenza, Ebola, and hantaviruses (4,10). These viruses have been thought to generate genetic diversity necessary for successful evolution, via mutation and reassortment of those with segmented genomes (19). Nevertheless, NSRV pathogens originating from HR and circulating in the field have been reported in influenza (12,13), Ebola (26), and hantaviruses (19,21).…”
mentioning
confidence: 99%
“…These viruses have been thought to generate genetic diversity necessary for successful evolution, via mutation and reassortment of those with segmented genomes (19). Nevertheless, NSRV pathogens originating from HR and circulating in the field have been reported in influenza (12,13), Ebola (26), and hantaviruses (19,21). Coinfection experiments have also confirmed that HR can occur in the hantaviruses of the Bunyaviridae family (19).…”
mentioning
confidence: 99%
See 1 more Smart Citation